Qualitative exploration of the experience of flow in ballet dancers who perform it as a hobby - De Priego, Melisa Khoury Miguel (2023)
There are numerous investigations on the psychological aspects related to the experience of flow in sport. However, the number of works on this subject in ballet dancers is scarce. This study, therefore, aims to explore the qualitative experience of flow in 10 ballet dancers who practice it as a hobby, from different schools in Metropolitan Lima, Peru. The study uses a descriptive phenomenological analysis, where through focused interviews it was possible to interview participants on different topics of interest based on their experience of flow. The results indicated that participants expressed themselves through the use of metaphors, emphasizing the internalisation of music when dancing, and giving importance to being in the “here and now” when they performed this activity. Emphasis is also placed on positive emotions and self-confidence when dancing, along with the influence of the environment to give the flow experience. Lastly, this experience manifests itself as unique and individual in each participant, where they describe it as a state that allows them to forget everything external, by concentrating solely on the dance.